IDEOLOGICAL STRUGGLE BETWEEN THE NATIONAL INTELLIGENTSIA AND BOLSHEVIKS IN THE EDUCATION SYSTEM OF UZBEKISTAN - Rashidov Oybek Rasulovich (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
In the following article some aspects of ideological struggle between the national intelligentsia and bolsheviks in the education system in Uzbekistan are revealed based on the periodicals and the available archive database. Modernistic solution to factors is analyzed